2015
DOI: 10.1016/j.cplett.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure prediction from first principles: The crystal structures of glycine

Abstract: Here we present the results of our unbiased searches of glycine polymorphs obtained using the Genetic Algorithms search implemented in Modified Genetic Algorithm for Crystals coupled with the local optimization and energy evaluation provided by Quantum Espresso. We demonstrate that it is possible to predict the crystal structures of a biomedical molecule using solely first principles calculations. We were able to find all the ambient pressure stable glycine polymorphs, which are found in the same energetic ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Density-functional approximations (DFAs), which have been some of the most promising tools for ranking the stability of possible crystal structures have also developed considerably, with many new van der Waals (vdW)-inclusive methods (Klimeš & Michaelides, 2012) particularly suited to modelling molecular materials (Reilly & Tkatchenko, 2015;Kronik & Tkatchenko, 2014;Brandenburg & Grimme, 2014). New developments in CSP codes and algorithms have also been reported (Habgood et al, 2015;Wang et al, 2012;Lund et al, 2015;Obata & Goto, 2015), while there have been a number of new insights into conformational polymorphism (Cruz-Cabeza & Bernstein, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Density-functional approximations (DFAs), which have been some of the most promising tools for ranking the stability of possible crystal structures have also developed considerably, with many new van der Waals (vdW)-inclusive methods (Klimeš & Michaelides, 2012) particularly suited to modelling molecular materials (Reilly & Tkatchenko, 2015;Kronik & Tkatchenko, 2014;Brandenburg & Grimme, 2014). New developments in CSP codes and algorithms have also been reported (Habgood et al, 2015;Wang et al, 2012;Lund et al, 2015;Obata & Goto, 2015), while there have been a number of new insights into conformational polymorphism (Cruz-Cabeza & Bernstein, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches to crystal structure generation which have been applied to molecular crystals include simulated annealing 30 and more sophisticated 31 variants of Monte Carlo searches and genetic algorithms, 3234 as well as the early pioneering CSP studies using purely random or grid searches. 3537 In fact, these simplest methods have been remarkably successful, consistently performing well in the structure searching aspect of the blind tests of CSP.…”
Section: Introductionmentioning
confidence: 99%
“…However, independently of the diffraction experiments, theoretical work had been carried out to assess the predictive power of a newly developed crystal structure prediction (CSP) workflow using glycine as the test case. Although a number of CSP surveys of glycine have been described (Zhu et al, 2012;Lund et al, 2015;Chisholm et al, 2005), none has so far identified candidates which fit the experimental data for -glycine, though a combined CSPpowder diffraction study has very recently yielded the crystal structure of glycine dihydrate (Xu et al, 2017).…”
Section: Crystal Structure Predictionmentioning
confidence: 99%